Anthropology of Aging: Maintaining the Autonomy of Older People and Improving Care through Narrative-based Bioethics (Revista Iberoamericana de Bioética, 2020)
In this article we focus on the issue of caring for the elderly from a philosophical- anthropological perspective. Through a phenomenological approach, we will provide the keys to improve the practice of caring, highlighting the bioethical aspects involved. As a person loses autonomy and independence, due to debilitating effects of old age, situations involving manipulation on the part of relatives, professionals and institutions may arise. Finally, we show how narrative-based Bioethics might raise awareness among professionals and families of the importance of empathy, caring and respecting bioethical limits to protect the elderly in situations of vulnerability.
Keywords: anthropology of aging; autonomy; dependence; vulnerability; narrative bioethics